Antibody C219 recognizes an α-helical epitope on P-glycoprotein - van den Elsen, Jean M. H. (National Academy of Sciences, 1999)
The ABC transporter, P-glycoprotein, is an integral membrane protein that mediates the ATP-driven efflux of drugs from multidrug-resistant cancer and HIV-infected cells. Anti-P-glycoprotein antibody C219 binds to both of the ATP-binding regions of P-glycoprotein and has been shown to inhibit its ATPase activity and drug binding capacity. C219 has been widely used in a clinical setting as a tumor marker, but recent observations of cross-reactivity with other proteins, including the c-erbB2 protein in breast cancer cells, impose potential limitations in detecting P-glycoprotein. We have determined the crystal structure at a resolution of 2.4 Å of the variable fragment of C219 in complex with an epitope peptide derived from the nucleotide binding domain of P-glycoprotein. The 14-residue peptide adopts an amphipathic α-helical conformation, a secondary structure not previously observed in structures of antibody–peptide complexes. Together with available biochemical data, the crystal structure of the C219-peptide complex indicates the molecular basis of the cross-reactivity of C219 with non-multidrug resistance-associated proteins. Alignment of the C219 epitope with the recent crystal structure of the ATP-binding subunit of histidine permease suggests a structural basis for the inhibition of the ATP and drug binding capacity of P-glycoprotein by C219. The results provide a rationale for the development of C219 mutants with improved specificity and affinity that could be useful in antibody-based P-glycoprotein detection and therapy in multidrug resistant cancers.